A study of noise levels on types of building construction works / Nurul Atiqah Mohd Hiffni - Mohd Hiffni, Nurul Atiqah (Faculty Architecture, Planninng and Surveying, 2014)
The construction sector is a vital part of the economy in most country, yet it is usually considered to be dirty, dangerous, unreliable, and hard. Construction and noise is very synonym together and it often cause people to make a complaint. As a developing country, Malaysia actively carrying out various construction activities such as construction of roads, administrative buildings, and also residential projects and an increase in activity can affect the safety and health of the parties involved. Although some steps have been taken to reduce the noise level at the area of the local community, but there are still a complained made by the community. The aim of this research is to find out the types of construction works that contribute to noise pollution and the objectives of the study are to identify the level of noise at the construction site, to identify the types of construction works that contribute to certain level of noise, and to identify whether noise from the construction works affects the people staying near the construction site. Noise pollution from construction sites is one of the major sources of noise pollution other than noise pollution from vehicles. High noise levels can lead to discomfort and negative effects to surrounding people. Therefore, a study was conducted to analyze the level of noise generated from the case study area. There are two methods used in this study, first the noise measurement conducted in three residential areas in Shah Alam which is near to the construction site by using Sound Level Meter (SLM) and the second method is in form of questionnaire to determine the level of noise exposure of the case study area to residents living near the construction site. The highest reading noise level using Sound Level Meter (SLM) among the 3 case study is at 10.30 am with 079 dB which is at iCity, followed by at 9.15 am with 078 dB also at iCity and the lowest noise level is at 9.30 am and 5.45 pm with 045 dB at Desa Alam